Vikings as a Concept: Etymological, Historical, and Cultural Approaches to Origin and Evolution - Vladislav O. Martynenko (СибСкрипт)
The article contains a systematic in-depth examination of key approaches to the concept of Vikings in historical science with a focus on its origin and evolution. Scandinavian historical studies and linguistics know the etymological, historical, and cultural approaches to Vikings as a term and a concept. The historicalgenetic, comparative-historical, and content-analytical research methods made it possible to reveal its etymology and diachronic concept signs. Both foreign and domestic historiography, as well as Scandinavian and Icelandic historical sources, prove that the etymological approach alone cannot provide a full understanding of this concept because it had a different semantics in the Viking age. Only in sagas did it acquire its key features of seafarers, looters, gangs, etc. These features correspond to the historical approach to the concept. The Scandinavian nationbuilding process in the 19th century blurred the line between the historical and cultural approaches: the term Vikings started to be applied to all peoples of Scandinavian origin engaged in trade, colonization, and looting. Today, most researchers use it as an umbrella term for all Scandinavians of the VIII–XI centuries.